The effect of feeding different levels of Aureomycin® in a mineral mixture to stocker cattle grazing native grass - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1994)
Two hundred and forty-three mixed breed steers were allotted to four treatments with two pastures per treatment. Treatments consisted of a free-choice mineral supplement alone or with Aureomycin® added to provide 150, 300, or 450 mg/hd/day. Gain was similar for all four treatments. The percentage of cattle with eye problems was reduced in pastures where 150 and 450 mg of Aureomycin were consumed daily; however, the incidence in the 300 mg/hd/day group was as high as in the control group.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Aureomycin®; Antibiotic; Mineral; Chlortetracycline; Native grass; Stocker cattle